1967
DOI: 10.1002/1097-0142(1967)20:1<51::aid-cncr2820200108>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and oxygenation of tumors in mice.I. Effects of breathing gases containing carbon dioxide at atmospheric pressure

Abstract: Inhalation of 5% carbon dioxide (CO2) and 95% oxygen (O2) or 10% CO2 and 90% O2 at one atm pressure increased blood flow of the C3HBA isotransplant and C3H isoimplant in C3H mice compared with animals breathing 100% O2 or air. Oxygen concentration, measured by a platinum microelectrode, was improved in anoxic areas of the tumor when the animals inhaled the gases containing CO2 compared with those breathing 100% O2 or air; the relative increase was less when the electrode was placed in a well‐vascularized area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

1967
1967
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…Using the C3HBA mammary carcinoma implanted subcutaneously in mice as a tumour model, Kruuv et al (1966) showed that carbogen breathing resulted in a 20% increase in TBF compared to air breathing. Allowing the mice to breathe 10% CO 2 -90% O 2 caused blood flow to increase by an average of 50% (Kruuv et al, 1966). Similarly, it was recently shown that carbogen breathing for 6 min resulted in a 50-70% increase in blood flow in RIF-1 tumours growing subcutaneously in mice (Honess and Bleehen, 1995).…”
Section: Effects Of Different O 2 -Co 2 Breathing Mixtures On Tad Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the C3HBA mammary carcinoma implanted subcutaneously in mice as a tumour model, Kruuv et al (1966) showed that carbogen breathing resulted in a 20% increase in TBF compared to air breathing. Allowing the mice to breathe 10% CO 2 -90% O 2 caused blood flow to increase by an average of 50% (Kruuv et al, 1966). Similarly, it was recently shown that carbogen breathing for 6 min resulted in a 50-70% increase in blood flow in RIF-1 tumours growing subcutaneously in mice (Honess and Bleehen, 1995).…”
Section: Effects Of Different O 2 -Co 2 Breathing Mixtures On Tad Andmentioning
confidence: 99%
“…A common current approach has been the breathing of hyperoxic gases, including 100% oxygen (O 2 ) and carbogen (95% O 2 and 5% CO 2 ). The rationale for the use of carbogen over 100% O 2 is based on the following putative mechanisms: (1) CO 2 blocks hyperoxia-induced vasoconstriction, (2) increased CO 2 tensions cause a rightward shift of the oxygen-haemoglobin dissociation curve and (3) CO 2 has a positive chronotropic effect (Kruuv et al, 1966). Despite these sound theoretical grounds, the inhalation of carbogen has had only moderate success as a radiosensitizer (Siemann et al, 1977;Overgaard, 1989;Rojas, 1991).…”
mentioning
confidence: 99%
“…Many tumours have poor vascularity and tend to be resistant to radiotherapy and chemotherapy because of factors ranging from intrinsic genetic resistance to extrinsic physiological factors (as reviewed by Vaupel et al, 1989). As some studies have shown that it is possible to enhance tumour blood flow and/or oxygenation by carbogen (95% oxygen/5% carbon dioxide) breathing in animals (Kruuv et al, 1967;Honess et al, 1995;Robinson et al, 1995) and humans (Falk et al, 1992), the effects of carbogen breathing on IF pharmacokinetics were also studied. Carbogen breathing has also been shown to increase the efficacy of radiotherapy (Rojas 1991).…”
mentioning
confidence: 99%
“…The radiosensitivity of tumors can be improved by increasing tumor oxygen levels, which can be achieved by breathing high-oxygen-content gases [15,26,30]. Addition of CO 2 to O 2 was thought to prevent intermittent vascular closure, thereby improving perfusion, or act on tumor metabolism, resulting in a further improvement of tumor oxygenation [25,27,31,38]. For head-and-neck tumors, breathing a hyperoxic hypercapnic gas mixture like carbogen (95% O 2 , 5% CO 2 ) in combination with nicotinamide administration resulted in a significantly improved tumor response to accelerated radiotherapy (accelerated radiotherapy with carbogen and nicotinamide [ARCON]) [19,20].…”
Section: Introductionmentioning
confidence: 99%